Through ethnographic studies and character education values to introduce the Teratai Putih martial arts college - Maulani Khofifa; I Ketut Budaya Astra; I Gede Suwiwa (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
This study aims to reintroduce the profile and history of the Teratai Putih Pencak Silat College located in Sukasada Village, Sukasada District, Buleleng Regency to the wider community as well as the implementation of character education values at the Teratai Putih Pencak Silat College. This type of research is qualitative research using an ethnographic approach. The professors, trainers, and fighters of the Teratai Putih Pencak Silat College became the subjects of this research to obtain valid data. Data collection techniques were carried out by triangulation of data using 3 techniques, namely the participatory observational process, in-depth interviews, and document research. The research tool uses interview guidelines. The stages of data analysis techniques include data collection, data reduction, data presentation, and validation. The results showed that the Teratai Putih pencak silat College had existed since August 1971 and was chaired by professor Jero Nyoman Sudiadnyana along with 3 other people, namely Komang Pica, Made Duara and Gede Sujayasa, who in 1980 was officially registered at IPSI Buleleng. The application of the values of character education at the Teratai Putih Pencak Silat College has been realized since the beginning of the establishment of this college.